2017
DOI: 10.3389/fimmu.2017.01361
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Maturation of a Humanized Shark VNAR Domain to Improve Its Biophysical Properties to Facilitate Clinical Development

Abstract: Molecular engineering to increase the percentage identity to common human immunoglobulin sequences of non-human therapeutic antibodies and scaffolds has become standard practice. This strategy is often used to reduce undesirable immunogenic responses, accelerating the clinical development of candidate domains. The first humanized shark variable domain (VNAR) was reported by Kovalenko and colleagues and used the anti-human serum albumin (HSA) domain, clone E06, as a model to construct a number of humanized vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 42 publications
0
44
0
Order By: Relevance
“…We have previously reported superior in vitro and in vivo efficacy of the anti-TNF-α Quad-X™ over Humira® and have shown that much of this 10x improvement in potency is due to the empirical design of the Quad-X™ format [22,28]. The low inherent immunogenicity of the VNAR domains and its humanised soloMER™ derivatives has been previously confirmed experimentally [21]. Here, the serum levels of Humira® in treated mice were lower compared with the Quad-X™-treated samples, with the 1 mg/kg Humira® group showing a severe depletion in drug levels in the pooled serum samples (Figure 1(a) and 2(a)).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We have previously reported superior in vitro and in vivo efficacy of the anti-TNF-α Quad-X™ over Humira® and have shown that much of this 10x improvement in potency is due to the empirical design of the Quad-X™ format [22,28]. The low inherent immunogenicity of the VNAR domains and its humanised soloMER™ derivatives has been previously confirmed experimentally [21]. Here, the serum levels of Humira® in treated mice were lower compared with the Quad-X™-treated samples, with the 1 mg/kg Humira® group showing a severe depletion in drug levels in the pooled serum samples (Figure 1(a) and 2(a)).…”
Section: Discussionmentioning
confidence: 83%
“…The novel anti-hTNF-α VNAR Quad-X™ is a 103 kDa engineered domain with two biparatopic anti-hTNF-α VNAR domains (VNAR D1 and C4) fused to the hinge region of a wildtype human IgG1 Fc via a short glycine-rich linker, and two additional binding domains (VNAR D1 and C4) Cterminally fused to the CH-3 region of the Fc fragment via a longer flexible glycine-rich linker creating a quadrivalent/biparatopic construct harbouring a wild-type human IgG1 Fc fragment. A second anti-hTNF-α VNAR drug D1-NDure™-C4 is a 38 kDa linear bispecific construct of the two anti-hTNF-α VNAR D1 and C4 domains, respectively, fused via flexible glycine-rich linkers to the N-and C-terminal regions of a humanised anti-human serum albumin VNAR, NDure™ [21,22,28,29]. This linear construct incorporates a c-terminal poly-histidine tail and a protein-L binding site in the framework region of the HSA binding partner (NDure™) allowing flexibility for downstream immunodetection and purification.…”
Section: Protein Drug Formats and Endotoxinmentioning
confidence: 99%
See 1 more Smart Citation
“…The lead clones were assessed for any tendency to dimerize, tolerance to N-and C-terminal fusions, stability, affinity and relative antigenicity in human dendritic cell assays. In addition, the functionality of the clones was verified in vivo through the extension of serum half-life in a typical drug format [66]. From these analyses, a clone known as BA11 showed insignificant antigenicity, high affinity and high stability for mouse, rat and HSA.…”
Section: Formatting and Humanization Of Vnarmentioning
confidence: 99%
“…From these analyses, a clone known as BA11 showed insignificant antigenicity, high affinity and high stability for mouse, rat and HSA. When these attributes were combined with demonstrable functionality in a rat model of pharmacokinetics, the BA11 was established as their clinical candidate [66].…”
Section: Formatting and Humanization Of Vnarmentioning
confidence: 99%